Environmentally friendly electric vehicle design - Mairuhu, Daffa Renaldhi Chaniago (Institute for Advanced Science Social, and Sustainable Future, 2024)
Particularly for automobiles, the global automotive industry is expanding quickly. One of the most often used forms of transportation in Indonesia is the automobile. A variety of cars, including MPVs, SUVs, City Cars, and Sedans, each with the sophistication and benefits of its own type, are being supplied by producers of four-wheeled vehicles. With a focus on sustainability and minimalism, designers create designs for city cars. This essay's goal is to examine how the environmentally friendly City Car is used in cities. The writing uses analytic techniques, design sketches, and three-dimensional visual representations.